(untitled) (Research, Society and Development, 2020)
We sought to characterize the profile of adolescent morbidity and mortality from exogenous intoxication in Brazil in the last decade. It is a documentary, descriptive, time series analysis with a quantitative approach, carried out in August 2020, through the Information System for Notifiable Diseases (SINAN) of the Informatics Department of the Unified Health System (DATASUS). The data were processed in the programs: TabWin version 4.14, Microsoft Excel version 2016 and Microsoft Office. A total of 198,367 notifications were found in the period from 2010 to 2019. The Southeast region and the state of São Paulo occupied the first place with 95,250 and 37,916 records, respectively. The cases were concentrated in the urban area (87.62%) and in the age group between 15 and 19 years old (73.40%). The female sex was the most expressive (67.25%) and the white race prevailed (40.03%). The medication was the main toxic agent (53.53%) and suicide attempt was the main circumstance (52.01%). Most of the exposures were of the acute type (65.49%), with the most used confirmation criterion being the clinical (63.31%). A total of 155,915 cases evolved to cure without sequelae and 131,237 were classified as confirmed intoxication. Exogenous intoxication in adolescents in Brazil has as its protagonist white girls, aged between 15 and 19 years, living in the urban area of ​​large cities, who use abruptly and only high doses of drugs as a suicide attempt method.